Effect of Operating Stresses on Elements of Shovel Swing Bearings; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Horeshok A. A.; Bogomolov I. D.; Buyankin P. V.; Vorobyev A. V. Aleksey Vasilievich (Designing and Modelling of Machines and Mechanisms, 2015)
Title screen